Perancangan Jaringan Rantai Pasok Dan Sistem Informasi Pemasaran Pada Program Sistem Ekonomi Jaringan Usaha Koperasi Untuk Kerjasama Usaha Koperasi - Azhar Solihin, Shofwan; Ezra, Ezra (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Cooperatives are an opportunity for economic actors to continue to develop with business activities carried out in groups to achieve common goals among fellow cooperative members, so strategic planning in the form of a design for a Government Program, especially in the Cooperative Sector, is a form of consideration and input for developing a resource. The resources owned by cooperatives in Bandung City by providing digital trade, from the Cooperative Business Network Economic System Program, abbreviated as SEJUK, with the aim of creating business cooperation between cooperatives in Bandung City. Information collection and management carried out in the form of interviews, literature studies, design carried out using quantitative research methods, marketing information system design based on Unified Modeling Leangues (UML) and supply chain planning based on Value Stream Mapping (VSM). From the design results, it is clear that supply chain network design and marketing information systems are connected in managing cooperatives to carry out goods procurement and business promotion activities by utilizing marketing information systems to provide digital trade channels for cooperatives participating in the SEJUK Program. so that the impact given by participating in the SEJUK Program needs to be improved and enhanced in the future in providing a forum for cooperatives to carry out business collaboration through the SEJUK Program